2021
DOI: 10.2169/internalmedicine.7611-21
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone-associated Pseudolithiasis in Elderly People: Frequency and Risk Factors

Abstract: Objective Ceftriaxone (CTRX) is a widely used antibiotic because of its long plasma half-life and good tissue transmission. Many of the reported studies on CTRX-associated pseudolithiasis were performed in children. Although some studies have been published in adults, there are no studies limited to elderly people. The present study investigated CTRX-associated pseudolithiasis and explored its risk factors in the elderly. Methods We retrospectively reviewed 133 elderly patients (" 65 years old) treated with CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…These findings suggest that special attention should be paid to the degree of oral intake and patient activity when CTRX is prescribed. Additional predisposing factors of pseudolithiasis in elderly patients include the dose of CTRX, duration of treatment, and the presence of renal dysfunction [ 4 , 14 ]. In our current case, old age, fasting, dehydration, long-term bed rest, and high-dose CTRX were the predisposing factors of CTRX-related pseudolithiasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that special attention should be paid to the degree of oral intake and patient activity when CTRX is prescribed. Additional predisposing factors of pseudolithiasis in elderly patients include the dose of CTRX, duration of treatment, and the presence of renal dysfunction [ 4 , 14 ]. In our current case, old age, fasting, dehydration, long-term bed rest, and high-dose CTRX were the predisposing factors of CTRX-related pseudolithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…CTRX-related pseudolithiasis is frequent in children [ 3 ]. However, recent reports have shown a high incidence of CTRX-induced pseudolithiasis in older people [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have also reported CTRX-associated biliary pseudolithiasis in adults. Risk factors for pseudolithiasis include limited activity or increased dehydration risk in elderly individuals, a cumulative CTRX dose exceeding 19 g, and prolonged CTRX treatment [ 37 ]. Pseudolithiasis formation occurs within 2–48 days after initiating CTRX treatment [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can sometimes induce biliary sludge or stone formation as a Calcium-Ceftriaxone salt, because of the interaction with Calcium ions (Katzung, 2018;Shiffman et al, 1990;Park et al, 1991;Schmutz et al, 2011). Most of the cases affected by this condition are adults and elderly people but also children can develop it (Yoshida et al, 2019;Hotta et al, 2021;Papadopoulou et al, 1999;Prince and Senac, 2003;Ozturk et al, 2005;Araz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%